Inflammation Meets Metabolic Disease: Gut Feeling Mediated by GLP-1 - Zietek, Tamara; Rath, Eva (Frontiers in Immunology, 2016)
Chronic diseases such as obesity and diabetes, cardiovascular and inflammatory bowel diseases (IBD) share common features in their pathology. Metabolic disorders exhibit strong inflammatory underpinnings and vice versa, inflammation is associated with metabolic alterations. Next to cytokines and cellular stress pathways like the unfolded protein response (UPR), alterations in the enteroendocrine system are intersections of various pathologies. Enteroendocrine cells (EEC) have been studied extensively for their ability to regulate gastrointestinal motility, secretion, and insulin release by release of peptide hormones. In particular the L cell-derived incretin hormone glucagon-like peptide 1 (GLP-1) has gained enormous attention due to its insulinotropic action and relevance in the treatment of type 2 diabetes (T2D). Yet, accumulating data indicates a critical role for EEC and in particular for GLP-1 in metabolic adaptation and in orchestrating immune responses beyond blood glucose control. EEC sense the lamina propria and luminal environment including the microbiota via receptors and transporters. Subsequently mediating signals by secreting hormones and cytokines, EEC can be considered as integrators of metabolic and inflammatory signaling. This review focuses on L cell and GLP-1 functions in the context of metabolic and inflammatory diseases. The effects of incretin-based therapies on metabolism and immune system are discussed and the interrelation and common features of metabolic and immune-mediated disorders are highlighted. Moreover, it presents data on the impact of inflammation, in particular of IBD on EEC and discusses the potential role of the microbiota as link between nutrients, metabolism, immunity and disease.